2014
DOI: 10.1001/jamadermatol.2013.6675
|View full text |Cite
|
Sign up to set email alerts
|

Staging for Cutaneous Squamous Cell Carcinoma as a Predictor of Sentinel Lymph Node Biopsy Results

Abstract: Our findings suggest that most cSCCs associated with positive SLNB findings occur in T2 lesions (in both staging systems) that are greater than 2 cm in diameter. The alternative staging system appears to more precisely delineate high-risk lesions in the T2b category that may warrant consideration of SLNB. Future prospective studies are necessary to validate the relationship between tumor stage and positive SLNB findings and to identify the optimal staging system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…The majority of positive SLNBs were AJCC T2 stage tumors (13 out of 116 SLNs; 11.2%) and BWH stage T2b tumors (5 out of 17 SLNs; 29.4%) while no AJCC or BWH stage T1 and only 6 out of 85 (7.1%) BWH stage T2a tumors had a positive SLN. Although more data is needed, the rate of positive SLNB in BWH stage T2b tumors far exceeds the 10% rate threshold for SLNB in malignant melanoma (66). A recent systematic review reported the rate of positive SLNB in CSCC patients as 13.9% (32 out of 231 patients) with a false negative rate of 4.6% (10 out of 215 patients).…”
Section: Sentinel Lymph Node Biopsy (Slnb)mentioning
confidence: 99%
“…The majority of positive SLNBs were AJCC T2 stage tumors (13 out of 116 SLNs; 11.2%) and BWH stage T2b tumors (5 out of 17 SLNs; 29.4%) while no AJCC or BWH stage T1 and only 6 out of 85 (7.1%) BWH stage T2a tumors had a positive SLN. Although more data is needed, the rate of positive SLNB in BWH stage T2b tumors far exceeds the 10% rate threshold for SLNB in malignant melanoma (66). A recent systematic review reported the rate of positive SLNB in CSCC patients as 13.9% (32 out of 231 patients) with a false negative rate of 4.6% (10 out of 215 patients).…”
Section: Sentinel Lymph Node Biopsy (Slnb)mentioning
confidence: 99%
“…This number rises to 50.0% when four risk factors are present. 27 In a recent systematic review, the authors successfully demonstrated the feasibility and reliability of SLNB for accurate staging of head and neck SCCS patients with a false omission rate of only 4.76%, similar to the experience with melanoma. 2 Indeed, SLNB use may improve survival rates in SCCS, not only by identifying subclinical lymph node involvement but by locating the correct draining nodal basin, which would guide directed therapy at an earlier and potentially more curable point of regional metastatic spread.…”
Section: Surgical Managementmentioning
confidence: 61%
“…Of those cSCCs that metastasize, 80% involve regional lymph nodes [5,25,27]. CSCCs can also metastasize to distant sites including the lungs, liver, brain, bones, and other cutaneous locations [27,28].…”
Section: Work Upmentioning
confidence: 99%
“…Of those cSCCs that metastasize, 80% involve regional lymph nodes [5,25,27]. CSCCs can also metastasize to distant sites including the lungs, liver, brain, bones, and other cutaneous locations [27,28]. The risk factors most often associated with metastasis include perineural invasion, recurrence after treatment, size greater than 2 cm, and poorly differentiated histology [6,29].…”
Section: Work Upmentioning
confidence: 99%
See 1 more Smart Citation